Characterization of two coleopteran alpha-amylases and molecular insights into their differential inhibition by synthetic alpha-amylase inhibitor, acarbose - Channale, Sonal M.; Bhide, Amey J.; Yadav, Yashpal; Kashyap, Garima; Pawar, Pankaj K.; Maheshwari, V. L.; Ramasamy, Sureshkumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2016)
Post-harvest insect infestation of stored grains makes them unfit for human consumption and leads to severe economic loss. Here, we report functional and structural characterization of two coleopteran alpha-amylases viz. Callosobruchus chinensis alpha-amylase (CcAmy) and Tribolium castaneum alpha-amylase (TcAmy) along with their interactions with proteinaceous and non-proteinaceous alpha-amylase inhibitors. Secondary structural alignment of CcAmy and TcAmy with other coleopteran alpha-amylases revealed conserved motifs, active sites, di-sulfide bonds and two point mutations at spatially conserved substrate or inhibitor binding sites. Homology modeling and molecular docking showed structural differences between these two enzymes. Both the enzymes had similar optimum pH values but differed in their optimum temperature. Overall, pattern of enzyme stabilities were similar under various temperature and pH conditions. Further, CcAmy and TcAmy differed in their substrate affinity and catalytic efficiency towards starch and amylopectin. HPLC analysis detected common amylolytic products like maltose and maltotriose while glucose and malto-tetrose were unique in CcAmy and TcAmy catalyzed reactions respectively. At very low concentrations, wheat alpha-amylase inhibitor was found to be superior over the acarbose as far as complete inhibition of amylolytic activities of CcAmy and TcAmy was concerned. Mechanism underlying differential amylolytic reaction inhibition by acarbose was discussed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Acarbose; alpha-amylase; alpha-amylase inhibitor; Callosobruchus chinensis; Coleoptera; Tribolium castaneum

Genomic and functional characterization of coleopteran insect-specific alpha-amylase inhibitor gene from amaranthus species - Bhide, Amey J.; Channale, Sonal M.; Yadav, Yashpal; Bhattacharjee, Kabita; Pawar, Pankaj K.; Maheshwari, V. L.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Plant Molecular Biology, 2017)
The smallest 32 amino acid alpha-amylase inhibitor from Amaranthus hypochondriacus (AAI) is reported. The complete gene of pre-protein (AhAI) encoding a 26 amino acid (aa) signal peptide followed by the 43 aa region and the previously identified 32 aa peptide was cloned successfully. Three cysteine residues and one disulfide bond conserved within known alpha-amylase inhibitors were present in AhAI. Identical genomic and open reading frame was found to be present in close relatives of A. hypochondriacus namely Amaranthus paniculatus, Achyranthes aspera and Celosia argentea. Interestingly, the 3'UTR of AhAI varied in these species. The highest expression of AhAI was observed in A. hypochondriacus inflorescence; however, it was not detected in the seed. We hypothesized that the inhibitor expressed in leaves and inflorescence might be transported to the seeds. Sub-cellular localization studies clearly indicated the involvement of AhAI signal peptide in extracellular secretion. Full length rAhAI showed differential inhibition against alpha-amylases from human, insects, fungi and bacteria. Particularly, alpha-amylases from Helicoverpa armigera (Lepidoptera) were not inhibited by AhAI while Tribolium castaneum and Callosobruchus chinensis (Coleoptera) alpha-amylases were completely inhibited. Molecular docking of AhAI revealed tighter interactions with active site residues of T. castaneum alpha-amylase compared to C. chinensis alpha-amylase, which could be the rationale behind the disparity in their IC50. Normal growth, development and adult emergence of C. chinensis were hampered after feeding on rAhAI. Altogether, the ability of AhAI to affect the growth of C. chinensis demonstrated its potential as an efficient bio-control agent, especially against stored grain pests.

Glycoprotein alpha-amylase inhibitor from Withania somnifera differentially inhibits various alpha-amylases and affects the growth and development of Tribolium castaneum - Kasar, Sainath S.; Marathe, Kiran R.; Bhide, Amey J.; Herwade, Abhijeet P.; Giri, Ashok P.; Maheshwari, Vijay L.; Pawar, Pankaj K. (PEST Management Science, 2017)
BACKGROUND: Identification and characterisation of plant defensive molecules enrich our resources to design crop protection strategies. In particular, plant-derived proteinaceous inhibitor(s) of insect digestive enzymes appear to be a safe, sustainable and attractive option. RESULTS: A glycoprotein having non-competitive alpha-amylase inhibitory activity with a molecular weight of 8.3 kDa was isolated and purified from seeds of Withania somnifera alpha-amylase inhibitor (WSAI). Its mass spectrometry analysis revealed 59% sequence coverage with Wrightide II-type alpha-amylase inhibitor from Wrightia religiosa. A dose-dependent inhibition of alpha-amylases from Aspergillus oryzae, Bacillus subtilis, Helicoverpa armigera and Tribolium castaneumwas recorded. Interestingly, WSAI did not inhibit human salivary alpha-amylase significantly. When adults of T. castaneum were fed with WSAI (1.6mg g(-1)), decrease inconsumption, growthandefficiency of conversion of ingested foodwas evident, along withover fourfold increases in feedingdeterrence index. Adecline inlarval residual alpha-amylase activity after feedingofWSAI resulted ina reduction in longevity of T. castaneum. CONCLUSION: The study reflects the significance of WSAI in affecting the overall growth and development of T. castaneum. Pre-and post-harvest pest resistive capability makes WSAI a potential candidate for insect pest management. Further, the effectiveness of this inhibitor could be explored either in formulations or through a transgenic approach. (C) 2016 Society of Chemical Industry

Novel bifunctional inhibitor of protease and α-amylase from Clitorea ternatea restricts the growth and development in Spodoptera frugiperda - Dongare, Pratiksha M.; Madage, Varsha A.; Deshpande, V. Neha; Joshi, Rakesh S.; Giri, Ashok P.; Pawar, Pankaj K. (International Journal of Biological Macromolecules, 2025)
An inhibitor molecule capable of inhibiting a wide range of digestive enzymes without affecting endogenous enzymes is always desirable. We report characterization of CteTAI (M.W. 14 kDa), a bifunctional inhibitor (BFI) protein from the seeds of Clitoria ternatea capable of inhibiting trypsin and alpha-amylase. It retains trypsin inhibition activity up to 60 degrees C and alpha-amylase inhibition up to 40 degrees C. Trypsin inhibition is stable across pH 1-12, while alpha-amylase inhibition is stable between pH 3-7. CteTAI is a noncompetitive inhibitor of trypsin and an uncompetitive inhibitor of alpha-amylase. It selectively inhibits proteases and alpha-amylases from various sources, without affecting alpha-amylase from human saliva and Bacillus spp. Proteomic analysis identified CteTAI as a bifunctional inhibitor exhibiting 41 % similarity to a bifunctional inhibitor from Sesbania bispinosa. Feeding Spodoptera frugiperda larvae with CteTAI-infused diet impaired energy metabolism, resulting in undernourished larvae and malformed adults incapable of flight and mating. Key nutritional indices (RGR, RCR, %ECI, %FDI) were severely reduced, indicating that CteTAI disrupts growth and development by inhibiting multiple protease and alpha-amylase isoforms. Biochemical characterization of newly identified CteTAI suggests its potential application in crop protection.
Keywords: alpha-Amylase inhibitors; Bifunctional inhibitor; Clitoria ternatea; Protease inhibitors; Spodoptera frugiperda